Stevia Beverage Consumption prior to Lunch Reduces Appetite and Total Energy Intake without Affecting Glycemia or Attentional Bias to Food Cues: A Double-Blind Randomized Controlled Trial in Healthy Adults. Issue 5 (3rd March 2020) - Stamataki, Nikoleta S; Scott, Corey; Elliott, Rebecca; McKie, Shane; Bosscher, Douwina; McLaughlin, John T
ABSTRACT: Background: Stevia is a zero-calorie alternative to caloric sugars. Substituting caloric sweeteners with noncaloric sweeteners reduces available energy, but their effects on appetite, subsequent food intake, and neurocognitive responses are still unclear. Objective: The aim was to examine whether sweetness with or without calories influences food intake, appetite, blood glucose concentrations, and attentional bias (AB) to food cues. Methods: This was a randomized, controlled, double-blind crossover study. Healthy participants [ n = 20; aged 27 ± 5 y, 55% female; BMI (kg/m 2 ): 21.8 ± 1.5] completed 5 visits, consuming 5 study beverages: 330 mL water (control, no sweet taste, no calories) and either 330 mL water containing 40 g glucose or sucrose (sweet taste; calories, both 160 kcal), maltodextrin (no sweet taste; calories, 160 kcal), or 240 ppm stevia (sweet taste, no calories). Glucose and stevia beverages were matched for sweetness. Subjective appetite ratings and blood glucose were measured at baseline and at 15, 30, and 60 min postprandially. At 15 min participants performed a visual-dot probe task to assess AB to food cues; at 30 min, participants were offered an ad libitum lunch; food intake was measured. Results: Subjective appetite ratings showed that preload sweetness and calorie content both affected appetite. The total AUC for glycemia was significantly higher after the caloric beverages (mean ± SD: maltodextrin, 441 ± 57.6; glucose, 462 ± 68.1; sucrose, 425 ± 53.6 mmol × min × L −1 ) compared with both stevia (320 ± 34.2 mmol × min × L −1 ) and water (304 ± 32.0 mmol × min × L −1 ) (all P < 0.001). Total energy intake (beverage and meal) was significantly lower after the stevia beverage (727 ± 239 kcal) compared with water (832 ± 198 kcal, P = 0.013), with no significant difference between the water and caloric beverages ( P = 1.00 for water vs. maltodextrin, glucose, and sucrose). However, food-related AB did not differ across conditions ( P = 0.140). Conclusions: This study found a beneficial and specific effect of a stevia beverage consumed prior to a meal on appetite and energy intake in healthy adults. This trial is registered at clinicaltrials.gov as NCT03711084.